STRESS LEVELS AND EXAM RESULT AT GASTROINTESTINAL LESSON IN SCHOOL OF NURSING - Istianah Istianah; Suci Noor Hayati; Budi Rustandi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction. Problem Based Learning is new learning method that can be positive or negative effected students to accept this method. STIKES Rajawali used this education system for nursing collages. The purpose of this study was to know relationship between stress level and exam result at gastrointestinal lesson with PBL in School of Nursing. Methods. This study used Cross sectional design. The numbers of sample of this study were 77 collages. Collecting data used Student Stress and Coping Intervention (SSCI) questioner. Also use check list question to measure learning outcome at Gatrointestinal lesson with Problem Based Learning’s system education. Univariable analyze used frequent distribution and bivarible for identified relation between variables used annova test. Result. Annova test’s result showed that there was significant difference between learning outcome and stress level with p point = 0,001 at midle stress’ level. Discussion. It is can become reference in PBL method with competence based curricula. Good stress management could improve learning outcome at problem based learning system education. Keywords: learning outcome, stress, problem based learning, nursing